-4(s-6)-3=9

Simple and best practice solution for -4(s-6)-3=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(s-6)-3=9 equation:


Simplifying
-4(s + -6) + -3 = 9

Reorder the terms:
-4(-6 + s) + -3 = 9
(-6 * -4 + s * -4) + -3 = 9
(24 + -4s) + -3 = 9

Reorder the terms:
24 + -3 + -4s = 9

Combine like terms: 24 + -3 = 21
21 + -4s = 9

Solving
21 + -4s = 9

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + -4s = 9 + -21

Combine like terms: 21 + -21 = 0
0 + -4s = 9 + -21
-4s = 9 + -21

Combine like terms: 9 + -21 = -12
-4s = -12

Divide each side by '-4'.
s = 3

Simplifying
s = 3

See similar equations:

| -(b-9)+2=3 | | 3u+4=2u-9 | | 20x+15=30x+10 | | 4(d+3)+2=10 | | 3(d-12)=d+24 | | 9b+10=1 | | 2p+8=6 | | 3x+26=x+4 | | 20+8=6 | | 2x-4x^2= | | 16-3t=-7t | | 18-5(x+1)=3(x-1) | | 10g-47-4g=16+3g | | 8x^3-6x+1=0 | | 22-4x=2x-4 | | w-5+3w=6w-1 | | 10c+5=4c-1 | | 3x+3=4x-6 | | 7(x-10)=21 | | 14*(2x+2)=1716+6*(x+2) | | x^2+6x+8=e^2 | | z^2+iz=0 | | 3.3x=6.5(10x+4) | | ln(2x^2+7x-4)=2+ln(x^2+x-12) | | -1+(2t+3)+2(t-3)= | | 7x+5=45+3x | | ln(x)+ln(x-3)=ln(40) | | 6(p-5)-(4p+9)=25 | | 11a+18b+6C+4C-4B-2A= | | 8x+17=25 | | 15-(y+6)=16 | | 2(4a+2)-3(2a-4)= |

Equations solver categories